2014
DOI: 10.1149/2.069406jes
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Thermal Implications in Mechanical Degradation of Lithium-Ion Battery Electrodes

Abstract: In a lithium-ion cell, heat generation and temperature evolution during operation pose a significant bearing on the mechanical degradation and cell performance. The thermal implications on the electrode mechano-electrochemical behavior have been elucidated. Crack formation due to diffusion-induced stress in the active particles has been analyzed. Temperature dependence of the mechanophysicochemical parameters has been taken into account. Total amount of diffusion-induced damage has been estimated for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…However, this trend is balanced by the decreased utilization as particle size increases, resulting is less stress due to the shortened time for stress generation. 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this trend is balanced by the decreased utilization as particle size increases, resulting is less stress due to the shortened time for stress generation. 13 …”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] For the diffusion-induced stress model, diffusion coefficient in solid phase is a key parameter to determine the concentration gradient in the particle, which in turn affects the stress generated. 9 However, there is a wide disparity in the measured diffusion coefficient of lithium in graphite, ranging from 10 −16 to 10 −11 m 2 /s.…”
mentioning
confidence: 99%
“…The complexity of the approach is in the accurate mapping of the field variables (like concentration) from the spherical grid to the spring network while accounting for large deformation of the spring network. The approach has previously been demonstrated for pristine low volumetric expansion active material like graphite [42][43][44][45][46][47] and high capacity electrode active material particles like silicon and tin with two-phase diffusion. 40,41 In this work, we extend the model to do a comparative analysis of the fracture map for two-phase versus single phase diffusion inside silicon while accounting for the presence of a surface film by adding an additional layer of springs with spring stiffness different from the active material to investigate the resulting change in fracture map.…”
Section: Methodsmentioning
confidence: 99%
“…21,46 The effect of ambient temperature on the evolution of diffusion-induced stress revealed that mechanical degradation is prone to occur more in low temperature operations. 47 Experimental characterization of microcrack evolution within active particles can …”
mentioning
confidence: 99%
“…Development of a reduced order model.-According to the authors, evolution of microcrack density occurs toward the beginning of the delithiation process. 21,47 Eventually, the amount of microcrack formation reaches a state of saturation, and no further increase in mechanical degradation is observed during subsequent discharge-charge cycles. Thus, an exponential increase in damage evolution followed by saturation can be successfully captured by Eq.…”
mentioning
confidence: 99%